Unexpected Pneumothorax During Painless Flexible Bronchoscopy Under Remimazolam Sedation: Two Case Reports and a Literature Review - Cong Luo; Ru‐Yi Luo (Clinical Case Reports)
ABSTRACT The timely recognition of pneumothorax during painless flexible bronchoscopy (PFB) can be challenging. This report describes two consecutive cases of pneumothorax following PFB, both of which were promptly identified and successfully treated. A sudden decrease in heart rate, combined with hypoxemia, is highly effective for detecting pneumothorax in patients undergoing PFB, with subcutaneous emphysema serving as a key auxiliary diagnostic sign. Remimazolam may provide significant clinical benefits in emergency situations during PFB by allowing patients to be quickly awakened to assist with diagnosis.